Analysis of junior high school students' critical thinking skills in solving HOTS questions viewed from learning style - Dewi, Aulia Rahma; Sa'dijah, Cholis; Rofiki, Imam; Mustakim, Siti Salina (Jurnal Kajian Pembelajaran Matematika, 2024)
Currently junior high school students' critical thinking abilities are relatively low. One way to optimize students' critical thinking skills is through HOTS (High Order Thinking Skills) questions. Students' critical thinking abilities in solving HOTS questions vary due to differences in learning styles. This research analyzes junior high school students' critical thinking abilities in solving HOTS questions regarding learning style. The research method used is descriptive qualitative. Data collection techniques were carried out by distributing questionnaires, tests, and interviews. The interactive analysis model uses data collection, reduction, display, and conclusion drawing/verification. The research results show that students with a visual learning style tend to write answers completely and systematically, can identify problems in a structured manner, and have high accuracy, so they often recheck students' answers. Students with an auditory learning style have difficulty writing complete and structured answers but have good storytelling skills and often explain answers verbally even though they do not write them in detail. Kinesthetic students tend to write answers in sketch form, only recording a few steps and do not double-check answers because they cannot sit still for too long